Prevalence and determinants of faecal carriage of carbapenem- and third-generation cephalosporin-resistant Enterobacterales: a cross-sectional household survey in northern VietnamResearch in context - Max van Wijk; Hoang Huy Tran; Bich Ngoc Thi Vu; Costanza Tacoli; Tu Cam Thi Nguyen; Quynh Dieu Pham; Thương Hong Thi Nguyen; Trang Thu Nguyen; Hien Anh Thi Nguyen; Tung Son Trinh; Thai Duy Pham; Huong Kieu Thi Tran; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: Antimicrobial resistance (AMR) is a silent pandemic causing 1.27 million deaths in 2019, disproportionately affecting low- and middle-income countries, but resistance among commensal microbiota and the determinants of carriage have not been widely reported. This cross-sectional household study aimed to determine the prevalence of carbapenem-resistant (CRE) and third-generation cephalosporin-resistant Enterobacterales (C3GRE) in a rural community in Ha Nam northern Vietnam, as well as the socio-demographic, behavioural, and environmental determinants of carriage. Methods: 1502 individuals across 324 households were surveyed between July 2018 and April 2019. Faecal samples were cultured on meropenem and ceftazidime supplemented media to identify CRE and C3GRE, respectively. Logistic regression models were used to explore risk factors for CRE and C3GRE carriage compared to susceptible strains. Findings: Colonisation with C3GRE and CRE was 94.0% (95% Confidence Interval (CI) 93.5%–94.4%) and 1.9% (1.6%–2.2%), respectively. The CRE prevalence was too low to explore determinants. Antibiotic use in the last month (adjusted OR 1.22 [95% CI 0.45–3.31]) and recent illness (aOR 1.48 [0.34–6.51]) were not associated with C3GRE carriage. Variables associated with C3GRE carriage were high-income (OR 0.29 [0.12–0.74]), worse sanitary conditions (aOR 4.35 [1.07–17.43]), and frequent beef consumption (aOR 6.56 [2.16–19.98]). A protective association between C3GRE carriage and animal husbandry was observed in children under 5-years (aOR 0.27 [0.09–0.84]). For participants 5-years and older, chicken consumption was associated with increased likelihood of C3GRE carriage (aOR 3.45 [1.45–8.22]), while a protective association was observed for regular tofu (aOR 0.32 [0.14–0.74]) and fermented food consumption (aOR 0.55 [0.31–0.96]). Interpretation: In this high-prevalence setting, colonisation with C3GRE was not associated with individual antibiotic use, while environmental exposures, including food and sanitary conditions, were associated with C3GRE colonisation. Further research is required to understand the mechanisms behind these associations. Funding: This work was supported by Oxford University Clinical Research Unit internal grants in Vietnam from the Wellcome Trust Africa Asia Programme core grants (2015-2022—106680/Z/14/Z, and 2022-2029—225167/Z/22/Z).